Perception Patterns Among Actors in Institutional Networks: The Regional Intelligence Community Forum (Kominda) in Preventing Potential Conflicts in Central Java Province - Sulaiman, Sulaiman; Ibrahim, Akmal; Arifin, Ansar; Sukri, Phil. (Journal of Management and Administration Provision, 2024)
The multi-actor interaction process in government activities, involving both governmental and non-governmental elements, inevitably involves differences in perception among actors to achieve a common agreement. This interaction is crucial in conflict prevention processes involving various cross-sector government elements. The potential for conflict within society necessitates the early role of intelligence in identifying potential conflicts. Thus, the government has established the Regional Intelligence Community Forum (Kominda) at both provincial and regency/city levels, including in Central Java Province. This study aims to analyze the perception patterns of the Regional Intelligence Community Forum (Kominda) in preventing potential conflicts in Central Java Province. This study employs a qualitative research method. Data collection methods include observation, in-depth interviews, focus group discussions (FGD), and document studies. Data sources consist of primary and secondary data. Data analysis utilizes an interactive data analysis method. Informants in this study are actors directly involved in the interaction processes of the Regional Intelligence Community Forum (Kominda) in preventing potential conflicts in Central Java Province. The study results indicate that differences in opinion within the Regional Intelligence Community Forum are infrequent due to the forum's nature of information sharing and coordination. Institutional actors in the forum share the same working principles and goals and have established emotional relationships, reducing sectoral ego. Each issue discussed in the forum consistently finds common ground and solutions through coordination. Therefore, it is necessary to enhance relationships and trust among actors involved in the Regional Intelligence Community Forum (Kominda) and to increase the intensity of both formal and incidental coordination and communication to maximize intelligence findings, making conflict prevention efforts in Central Java Province more effective.